From the Discovery of Extremozymes to an Enzymatic Product: Roadmap Based on Their Applications - Espina, Giannina; Muñoz-Ibacache, Sebastián A.; Cáceres-Moreno, Paulina; Amenabar, Maximiliano J.; Blamey, Jenny M. (Frontiers in Bioengineering and Biotechnology, 2022)
With the advent of the Industrial revolution, the use of toxic compounds has grown exponentially, leading to a considerable pollution of the environment. Consequently, the development of more environmentally conscious technologies is an urgent need. Industrial biocatalysis appears as one potential solution, where a higher demand for more robust enzymes aims to replace toxic chemical catalysts. To date, most of the commercially available enzymes are of mesophilic origin, displaying optimal activity in narrow ranges of temperature and pH (i.e. between 20°C and 45°C, neutral pH), limiting their actual application under industrial reaction settings, where they usually underperform, requiring larger quantities to compensate loss of activity. In order to obtain novel biocatalysts better suited for industrial conditions, an efficient solution is to take advantage of nature by searching and discovering enzymes from extremophiles. These microorganisms and their macromolecules have already adapted to thrive in environments that present extreme physicochemical conditions. Hence, extremophilic enzymes stand out for showing higher activity, stability, and robustness than their mesophilic counterparts, being able to carry out reactions at nonstandard conditions. In this brief research report we describe three examples to illustrate a stepwise strategy for the development and production of commercial extremozymes, including a catalase from an Antarctic psychrotolerant microorganism, a laccase from a thermoalkaliphilic bacterium isolated from a hot spring and an amine-transaminase from a thermophilic bacterium isolated from a geothermal site in Antarctica. We will also explore some of their interesting biotechnological applications and comparisons with commercial enzymes.